Recovery of the Cell Cycle Inhibition in CCl4-Induced Cirrhosis by the Adenosine Derivative IFC-305 - Victoria Chagoya de Sánchez; Lidia Martínez-Pérez; Rolando Hernández-Muñoz; Gabriela Velasco-Loyden (International Journal of Hepatology)
Introduction. Cirrhosis is a chronic degenerative illness characterized by changes in normal liver architecture, failure of hepatic function, and impairment of proliferative activity. The aim of this study is to know how IFC-305 compound induces proliferation of the liver during reversion of cirrhosis. Methods. Once cirrhosis has been installed by CCl4 treatment for 10 weeks in male Wistar rats, they were divided into four groups: two received saline and two received the compound; all were euthanized at 5 and 10 weeks of treatment. Liver homogenate, mitochondria, and nucleus were used to measure cyclins, CDKs, and cell cycle regulatory proteins PCNA, pRb, p53, E2F, p21, p27, HGF, liver ATP, and mitochondrial function. Results. Diminution and small changes were observed in the studied proteins in the cirrhotic animals without treatment. The IFC-305-treated rats showed a clear increase in most of the proteins studied mainly in PCNA and CDK6, and a marked increased in ATP and mitochondrial function. Discussion/Conclusion. IFC-305 induces a recovery of the cell cycle inhibition promoting recovery of DNA damage through the action of PCNA and p53. The increase in energy and preservation of mitochondrial function contribute to recovering the proliferative function.